Low level optimization of mobile Java application in increasing speed / Radde Idzwan Ab. Razak - Ab. Razak, Radde Idzwan (2004)
Nowadays, mobile devices have become essential devices for people to communicate with each other. Now it is a need for people to have it, not just some accessories to satisfy people want. Realizing the trends, mobile devices manufacturer had come out with variety of mobile phone extra features to capture the market as the market provide large amount of potential customer. One of the features is Java compliant. Mobile devices that are supporting Java application provide user with the availability of games which can be added anytime people want. As long the mobile devices is Java compliant, any application can be design to be use in the mobile phone. However, there are limitations in the amount of resources in mobile phone. The limitations cause the application is slower in execution time. Speeding up application is not typically a concern in the development of the application. In contrast, this situation is not true for Java application, especially for Java application for mobile devices. This gives us a reason to develop some kind set of programming tips which is better in increasing performance of the application. Author had tested and produces several techniques to optimize speed of mobile Java application at the end of this research. These techniques are suggested to be implementing during the development of the application in the coding phase.